Factors associated with latency period in preterm prelabor rupture of membranes. (17th August 2016) - Phupong, Vorapong; Kulmala, Lalita
Abstract: Objective : To determine the factors associated with prolonged latency periods in preterm prelabor rupture of membrane (PPROM). Methods : This retrospective study analyzed data from singleton pregnant women with gestational age between 28 and 34 weeks suffering from PROM. Multivariate regression analysis was used to evaluate the association between the factors and latency period ≥ 2 and ≥ 7 days. Results : A total of 231 cases of PPROM were included. Prolong latency period ≥2 and 7 days were achieved in 141 (61%) and 54 (23.4%) cases. Higher gestational age at PPROM and cervical dilatation >2 cm were associated with a shorter latency period <2 days. Multiparity and presence of uterine contraction at admission were associated with a shorter latency period <7 days. Prophylactic antibiotics [odds ratio (ORs) 6.69, 95% confidence interval (CI) 3.0–14.89], and tocolysis (ORs 2.74, 95%CI 1.25–6.02) were factors associated with latency period ≥ 2 days. Only prophylactic antibiotics (ORs 7.7, 95%CI 2.54–23.34) was a factor associated with latency period ≥7 days. Conclusions : Prophylactic antibiotics and tocolysis are two major factors associated with latency period ≥2 days in PPROM, where prophylactic antibiotics is the main factor associated with latency period ≥7 days in PPROM.